Thyroid Function and the Risk of Non-Alcoholic Fatty Liver Disease in Morbid Obesity - Borges-Canha, Marta; Neves, João Sérgio; Mendonça, Fernando; Silva, Maria Manuel; Costa, Cláudia; Cabral, Pedro M.; Guerreiro, Vanessa; Lourenço, Rita; Meira, Patrícia; Salazar, Daniela; Ferreira, Maria João; Pedro, Jorge; et al. (Frontiers in Endocrinology, 2020)
Background: An association between hypothyroidism and the risk of Non-alcoholic Fatty Liver Disease (NAFLD) has been suggested. This association remains to be elucidated in patients with morbid obesity. Aim: To evaluate the association between thyroid function and parameters of liver function and hepatic scores in patients with morbid obesity. Methods: Patients with morbid obesity followed in our centre between January 2010 and July 2018 were included. The ones without evaluation of liver and thyroid functions were excluded. Fatty Liver Index (FLI) and BARD scores were used as predictors of hepatic steatosis and fibrosis, respectively. Results: We observed a positive association between TSH and both BARD (OR 1.14; p=0.035) and FLI (OR 1.19; p=0.010) in the unadjusted analysis. We found a negative association between free triiodothyronine levels and BARD (OR 0.70; p<0.01) and a positive association between free triiodothyronine levels and FLI (OR 1.48; p=0.022). Concerning liver function, we found a positive association between total bilirubin and free thyroxine levels (β=0.18 [0.02 to 0.35]; p=0.033) and a negative association between total bilirubin and free triiodothyronine levels (β=-0.07 [-0.14 to -0.002]; p=0.042). Conclusion: Higher levels of TSH and free triiodothyronine may be associated with a higher risk of NAFLD, particularly steatosis, in patients with morbid obesity.